(untitled) - Short, Kenneth L. (Englewood Cliffs, New Yersey, 1991)
Book is an itegrated, unified and well-writen treatment of all the important hardware and software concepts currently in the design of effective microprocessor based system
Keywords: Vi xử lý,Microprocessors